Evaluation of fine needle aspiration cytology of cervical lymphadenopathy in Bir Hospital - Khadka, Subash; Shrestha, Deependra (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: To correlate FNAC of cervical lymphadenopathy with the histopathology. Materials and Methods: Prospective study on 67 patients with cervical lymphadenopathy at the ENT Department, Bir Hospital, from January 2013 to July 2014. Patients were subjected to both FNAC and histopathology. Results: Thirty cases (44.8%) were females and 37 cases (55.2%) were males. Tuberculosis was most common disease in 30(44.80%) patients. Sensitivity, specificity, and diagnostic accuracy of FNAC to diagnose tubercular lymphadenopathies were 83.0%, 100.0%, and 92.54% respectively. Overall correlation of FNAC to histopathology was 86.57%. Conclusion: FNAC is very simple and accurate technique for diagnosis of cervical lymphadenopathy. JCMS Nepal. 2015;11(1): 22-25